Quality of radiation conversion under four-wave mixing on thermal nonlinearity with feedback - A.A. Akimov; S.A. Guzairov; V.V. Ivakhnik (Компьютерная оптика, 2021)
Quality of radiation conversion under four-wave mixing on thermal nonlinearity with feedback for both signal and object waves has been investigated at high reflection coefficients. It has been shown that the optimal operating mode of a four-wave converter on thermal nonlinearity is the mode in which the pumping waves have equal intensities and there is a compensation for a phase shift arising from the pumping wave self-action. In this operating mode of the four-wave radiation converter, as compared with the case of the absence of feedback for both signal and object waves, a significant increase in the amplitude reflection coefficient is observed with an increase in the pumping waves intensities. In this case, despite the decrease in the bandwidth of spatial frequencies of the object wave with an increase in the pumping wave intensities, the quality of radiation conver-sion with feedback for both signal and object waves is better than in the absence of feedback.